CREDIT RISK DETERMINANTS OF COMMERCIAL BANKING - Handajani, Lilik; Akram, Akram; Sokarina, Ayudia (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
Studies on non-performing loans in banking provide mixed results regarding the bank-specific factors that influence them. This research aims to analyze the determinants of credit risk in commercial banking in Indonesia. Testing was conducted on 32 banking companies listed on the Indonesia Stock Exchange for 2019-2021 with 96 observations using panel data regression. The research results show that increasing bank diversification and external audit quality significantly reduce the risk of credit non-performing loans (NPL). Other findings of this research show that credit growth, operational efficiency, and bank size do not significantly affect credit risk. To overcome the problem of endogeneity and dynamic panel bias, a series of robustness tests were carried out using the 2SLS, LIML, and GMM approaches provided significant results. The results of this research imply that bank risk management plays a role in reducing problem loans, which must align with the business entity's efforts to increase profits.